Curriculum Reform in Quantity Surveying: Learner Insights for Enhancing Graduate Readiness in the Built Environment of Developing Countries - Jeffrey Boon Hui Yap; Jin Jin Ling; Martin Skitmore (Journal of Construction in Developing Countries, 2026)
This study examined the alignment of quantity surveying (QS) education with the evolving demands of the construction industry, particularly in developing countries. This study highlighted students’ perceptions of curriculum strengths, digital tool exposure and teaching quality of QS education programme structure, while identifying critical deficiencies in sustainability, communication, global readiness, and interdisciplinary collaboration in the education programme. A structured quantitative survey of 125 QS undergraduates from a leading and reputable private higher education institution in Malaysia was conducted to evaluate perceptions of educational adequacy across technical and human-centred competencies essential for the built environment. The originality of this study lies in its vertically integrated analysis across four academic levels, offering empirical insights seldom addressed in the literature. The findings present practical implications for higher education institutions, industry stakeholders, and policymakers by advocating a more integrated, forward-looking curriculum that promotes stronger academic-industry collaboration. Although the study was limited to a single institution, the results yield transferable insights for QS curriculum reform in comparable educational and developmental contexts. By foregrounding the student voice, this research contributes to ongoing discourse on educational innovation, sustainable capacity building, and the future of QS training within the architecture, engineering and construction industry in developing economies.